2015
DOI: 10.1038/onc.2015.131
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP2 potentiates nuclear EGFR–STAT3 signaling

Abstract: Insulin-like growth factor binding protein 2 (IGFBP2) is a pleiotropic oncogenic protein that has both extracellular and intracellular functions. Despite a clear causal role in cancer development, the tumor-promoting mechanisms of IGFBP2 are poorly understood. The contributions of intracellular IGFBP2 to tumor development and progression are also unclear. Here we present evidence that both exogenous IGFBP2 treatment and cellular IGFBP2 overexpression lead to aberrant activation of EGFR, which subsequently acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 88 publications
(72 reference statements)
3
65
0
Order By: Relevance
“…We treated U251 cells (which express endogenous IGFBP2) with the neutralizing antibody against IGFBP2. We recently demonstrated that IGFBP2 overexpression leads to activation of the EGFR/STAT3 signalling pathway in glioma cell lines . Treatment with the IGFBP2‐neutralizing antibody led to a reduction in the levels of phosphorylated (activated) EGFR and STAT3, as well as decreased expression of the STAT3 downstream target, Bcl‐xL (Figure A).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…We treated U251 cells (which express endogenous IGFBP2) with the neutralizing antibody against IGFBP2. We recently demonstrated that IGFBP2 overexpression leads to activation of the EGFR/STAT3 signalling pathway in glioma cell lines . Treatment with the IGFBP2‐neutralizing antibody led to a reduction in the levels of phosphorylated (activated) EGFR and STAT3, as well as decreased expression of the STAT3 downstream target, Bcl‐xL (Figure A).…”
Section: Resultsmentioning
confidence: 90%
“…A recent report described the development of a new neutralizing antibody against IGFBP2 ; further studies will be required to test this in a pre‐clinical model. We also recently demonstrated that siRNA‐based inhibition of IGFBP2 and mutation of the nuclear localization signal of IGFBP2 impaired glioma cell migration and invasion , demonstrating that IGFBP2 has nuclear roles in addition to secreted activities, findings that must be considered in assessing the therapeutic impacts of IGFBP2‐neutralizing antibodies. Alternative mechanisms for inhibiting IGFBP2 in a clinical setting include microRNA.…”
Section: Discussionmentioning
confidence: 98%
“…IGFBP-2 stimulates the nuclear form of epidermal growth factor receptor (EGFR), increasing the activated transcription factor 3 (STAT3) pathway. Moreover, overexpression of exogenous IGFBP-2 protein inhibits EGFR activity through suppression of nuclear EGFR signaling [24]. These results demonstrate a strong association between IGFBP-2 and STAT3 and suggest a novel tumor-inducing role for IGFBP2 by providing a linkage between IGFBP-2 and cancer development.…”
Section: Function Of Igfbps In Metabolic Signalingmentioning
confidence: 95%
“…Although IGFBP-2 is a secondary protein among the circulation binding proteins, the regulatory and functional roles of IGFBP-2 are not well understood compared to those of IGFBP-1. A recent study determined the role of IGFBP-2 to be a pleiotropic oncogenic protein in cancer development [24]. IGFBP-2 stimulates the nuclear form of epidermal growth factor receptor (EGFR), increasing the activated transcription factor 3 (STAT3) pathway.…”
Section: Function Of Igfbps In Metabolic Signalingmentioning
confidence: 99%
“…IGF-binding protein 2 (IGFBP2) is one of six proteins in the IGFBP family that bind IGFs with high affinity (8). IGFBP2 expression has been shown to be elevated in many cancer types in both tumor cells (913) and in the plasma (1416). Published studies showed that IGFBP2 was upregulated in pancreatic juice (17) and plasma (18) of PDAC patients.…”
Section: Introductionmentioning
confidence: 99%